The role of website format, blog use, and information-gathering acquaintance in online message assessment. Issue 4 (November 2015) - Greer, Jennifer; Pan, Po-Lin
Highlights Examining effects of website format, blog use and information-gathering acquaintance. Websites with higher credibility do not activate better online message perceptions. Information-gathering acquaintance and website format jointly affect online message perceptions. Mutual effects of blog use and website format are found on online message perceptions. Blog use is less relevant to online message perceptions than information-gathering acquaintance.